THE EFFECTIVENESS OF USING PHONETIC METHOD IN IMPROVING STUDENTS’ SPEAKING ABILITY - Suhardi Suhardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
This research is aimed at finding out the effectiveness of using the phonetic method in improving students’ speaking at civil vocational high school number four (SMKN 4) in Palopo. This research employed pre-experimental design. The population of this research is the first grade students at SMKN 4 Palopo. It consists of 2 classes and the total number of population is 41 students. This research used cluster sampling technique, the sample of this research is the class B where consists 20 students.  The instrument in collecting the data is speaking test. The treatment of this research is phonetic aspect in six times meeting, based on the data analysis, the writer find out the mean score of pretest is 36.80 it is classified very poor and mean score of posttest is 65.00 it is classified average. Its mean that data show students’ speaking ability is effective improve by using phonetic metod. The result of statistical analysis for level of significant (p=0.05) with degree freedom (df)=N-1, where (N-20), df=19. The probability value is smaller than α (0.00 < 0.05). It indicates that the alternative hypothesis (H1) is accepted and null hypothesis (H0) is rejected. The result give the confirmation about phonetic method can improve students’ ability in speaking.